Applications of continuous improvement methodologies in the voluntary sector: a systematic literature review. (17th February 2021) - Jevanesan, Thivya; Antony, Jiju; Rodgers, Bryan; Prashar, Anupama
Abstract : Despite the vast acceptance of continuous improvement (CI) methodologies in manufacturing and services industries, few organisations have implemented CI in the voluntary sector (VS). This paper presents a systematic review of the literature on CI methodologies in VS. 20 publications on the application of CI methodologies in VS were included drawn from four academic databases (EBSCOHost, Emerald Insight, Web of Science and Scopus). The review was restricted to peer-reviewed English-written academic articles published between 2000 and 2017. The findings revealed that cost reduction, increased customer satisfaction and improved staff empowerment are some of the potential benefits of implementing CI in the VS. Further, the possible challenges include resistance to change, lack of formal processes and the diversity of customers. This review underlines the critical success factors for the adoption of CI methodologies as appropriate leadership and organisational culture and staff engagement. Additionally, the paper identifies emerging trends and research gaps in this area. The findings of the study will enable VS professionals to gain a better understanding of the application of CI methodologies and will allow academics to conduct further research in this area using the identified research gaps.